2017
DOI: 10.1186/s12961-017-0178-8
|View full text |Cite
|
Sign up to set email alerts
|

Global toxocariasis research trends from 1932 to 2015: a bibliometric analysis

Abstract: BackgroundToxocariasis is a highly prevalent parasitic disease in the tropical regions of the world, with its impact on public health being typically underestimated. To better recognise the trends and characteristics of toxocariasis research, this study is a bibliometric analysis of the global toxocariasis research.MethodsSearches were completed on April 5, 2016, using the Scopus database. A search without any language restriction was performed to extract publications dealing with toxocariasis. Terms related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 60 publications
2
52
0
2
Order By: Relevance
“…No similar study has been found in a detailed literature search to address such those results but other related bibliometric studies have tried to make explanations for such findings [20][21][22]35]. A possible explanation for these findings may be referring to leishmaniasis prevalence rates which are higher in Tunisia and Sudan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No similar study has been found in a detailed literature search to address such those results but other related bibliometric studies have tried to make explanations for such findings [20][21][22]35]. A possible explanation for these findings may be referring to leishmaniasis prevalence rates which are higher in Tunisia and Sudan.…”
Section: Discussionmentioning
confidence: 99%
“…All leishmaniasis research publications published between January 1998 and December 2017 indexed on the Scopus database were analysed while the ones published in 2018 were excluded because Scopus as a secondary source has not yet archived all the publications from the primary sources for this year. The Scopus was used because it is the most widely accepted and frequently used database for analysis of scientific publications in different fields [22,[31][32][33][34]. The search was completed in November 2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11th Neufeld et al [66] "Reduced anxiety-like behavior and central neurochemical change in germ-free mice" [95], toxicology [28], social media in psychology [96], parasitic diseases [51,97], and viral diseases [98][99][100]. Additionally, it also reveals that researchers paid great attention on the MGBA mostly in recent years, and published several outstanding articles on top-ranking journals in the medical field such as Science [56] and Nature [64].…”
mentioning
confidence: 99%
“…[11] But after 2011 onwards specific research were conducted related to leishmaniasis in general; [12][13] or for specific countries and region such as Iran, [14][15] Latin America, [16] South America. [17] The bibliometric study focusing India were reported in parasitic and neglected tropical disease; [18] lymphatic filariasis; [19] and other neglected tropical diseases such as Ascariasis/Toxocariasis, [20] and Schistosomiasis. [21] However, these literature does not reveal any study covering the research impact of India in the field of leishmaniasis.…”
Section: Resultsmentioning
confidence: 99%